PENGARUH PENJUALAN, PERPUTARAN PIUTANG, DAN ARUS KAS TERHADAP LIKUIDITAS PADA PT UNILEVER INDONESIA Tbk - Rusdiyanto, Rusdiyanto (GEMA EKONOMI, 2019)
The research aims to examines and proves the influence of sales growth, receiveable turnover, and operating cash flow on the level of liquidity at PT Unilever Indonesia Tbk for period 2010-2018. This research used a quantitative method, using SPSS version 17. This study aims to find out and analyze the influence of sales growth, accounts receivable turnover, and operating cash flow on the level of liquidity at PT Unilever Indonesia Tbk for the period 2010-2018. This research uses a quantitative approach. The research results obtained are 1) Partial sales growth has no significant effect on the level of liquidity. 2) Partial receivable turnover does not have a significant effect on the level of liquidity. 3) Operating Cash Flow has an effect and significant to the level of liquidity. 4) Sales growth, receivable turnover, and operating cash flow simultaneously has an significant effect to the level of liquidity.DOI 10.5281/zenodo.3629926